Attitudes toward beef and vegetarians in Argentina, Brazil, France, and the USA. (1st January 2016) - Ruby, Matthew B.; Alvarenga, Marle S.; Rozin, Paul; Kirby, Teri A.; Richer, Eve; Rutsztein, Guillermina
Abstract: Meat is both the most favored and most tabooed food in the world. In the developed world, there is a tension between its high nutritional density, preferred taste, and high status on the one hand, and concerns about weight, degenerative diseases, the ethics of killing animals, and the environmental cost of meat production on the other hand. The present study investigated attitudes toward beef, and toward vegetarians, among college students in Argentina, Brazil, France, and the USA. Across countries, men were more pro-beef, in free associations, liking, craving, and frequency of consumption. By country, Brazil and Argentina were generally the most positive, followed by France and then the United States. Ambivalence to beef was higher in women, and highest in Brazil. Only Brazilian and American women reported frequent negative associations to beef (e.g. "disgusting", "fatty"). Overall, most students had positive attitudes to beef, and the attitude to vegetarians was generally neutral. America and Brazilian women showed some admiration for vegetarians, while only French men and women had negative attitudes to vegetarians. In spite of frequent negative ethical, health, and weight concerns, in the majority of the sample, liking for and consumption of beef was maintained at a high level. Highlights: We examined attitudes toward beef and vegetarianism in four cultures. Men were more pro-beef, in free associations, liking, craving, and consumption. The Argentines and French were most pro-beef. Ambivalence toward beef was highest among women and Brazilians. Most groups were neutral toward vegetarians; the French were most negative.